2013
DOI: 10.1902/jop.2012.120096
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of Potassium–Titanyl–Phosphate Laser and Photodynamic Therapy on Outcomes of Treatment of Chronic Periodontitis: A Randomized Controlled Clinical Trial

Abstract: In patients with CP, clinical outcomes from conventional periodontal treatment of deeper pockets can be improved by using adjunctive KTP laser.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
75
0
9

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(86 citation statements)
references
References 43 publications
2
75
0
9
Order By: Relevance
“…Similar findings were shown in a very recent randomized clinical trial 40 comparing the efficacy of potassium titanyl phosphate (KTP) laser and PDT in chronic periodontitis treatment. Contradictory results, however, were reported by a randomized clinical trial 41 investigating the efficacy of PDT, diode laser and deep scaling in the treatment of residual pockets and indicated that fewer infected pockets may remain after PDT or deep scaling than diode laser application after 6 months.…”
Section: Discussionsupporting
confidence: 82%
“…Similar findings were shown in a very recent randomized clinical trial 40 comparing the efficacy of potassium titanyl phosphate (KTP) laser and PDT in chronic periodontitis treatment. Contradictory results, however, were reported by a randomized clinical trial 41 investigating the efficacy of PDT, diode laser and deep scaling in the treatment of residual pockets and indicated that fewer infected pockets may remain after PDT or deep scaling than diode laser application after 6 months.…”
Section: Discussionsupporting
confidence: 82%
“…Five categories of lasers are included and described here. One laser type was not available in the United States (potassium titanyl phosphate), 75 and we did not include that laser. There are no standard operating protocols (such as power intensity and density, power, spot size, energy, repetition rate, tip size, pulsing versus continuous mode, mean energy loss, or time of application) for the lasers.…”
Section: Moderatementioning
confidence: 99%
“…General description of studies. Ten studies [75][76][77][78][79][80][81][82][83][84] published between 2008 and 2014 met the inclusion criteria for reporting the effect of SRP plus a PDT diode laser (wavelength, 660-810 nanometers) versus SRP alone. Six studies 75,76,79-82 were splitmouth trials, and 4 studies 77,78,83,84 were parallel-group trials.…”
Section: Moderatementioning
confidence: 99%
“…Eight out of the 18 studies have reported statistically significantly higher improvements in probing depth (PD) reduction and/or clinical attachment (CAL) gain following SRP + PDT compared to SRP alone, [21][22][23][24][25][26][27][28] _ENREF_22while the rest of 10 studies have failed to reveal statistically significant differences in these parameters. 29,[30][31][32][33][34][35][36][37][38] An additional improvement for the reduction of bleeding on probing (BOP) following the use of PDT was reported in 5 out of the 19 papers.…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%